EVALUASI KINERJA PADA PLATFORM TRANSPORTASI ONLINE DI INDONESIA - Muhammad Rizky Derianto; Nicky Akbar Ezzyzone; Helmina Helmina (LPPM Universitas Muhammadiyah Jambi, 2026)
Online transportation platforms have become an important part of urban mobility in Indonesia. However, the growth of ride-hailing services is followed by user complaints related to application reliability, price fairness, driver behavior, location accuracy, service security, and customer support. This article evaluates the performance of online transportation platforms in Indonesia using a literature-based approach. The evaluation model combines system quality, information quality, service quality, price perception, security, user satisfaction, and net benefit. The study reviews recent articles published within the last five years, especially studies discussing Gojek, Grab, and Maxim in several Indonesian cities. The analysis shows that platform performance cannot be measured only from the number of users or downloads. A platform is considered good when it is stable, easy to use, provides accurate information, offers fair prices, maintains security and privacy, and produces satisfaction and practical benefits for users. The findings also indicate that price/value perception and service quality often become dominant factors in shaping satisfaction, while system issues such as inaccurate pick-up points, application errors, and weak privacy protection can reduce user trust. This article recommends integrated performance improvement through application reliability, transparent pricing, driver service standardization, complaint handling, and continuous sentiment monitoring.